The application of multidisciplinary team combined flipped classroom teaching model in oral general course for clinical undergraduates - Xue-Jing Lin; Jie Zhou; Qing Yuan; Yu-Lei Dong; Wen-Xuan Xia; Diwas Sunchuri; Zhu-Ling Guo (BMC Medical Education)
Abstract Background Oral general course (OGC) is a basic subject of medical education. The implementation of multidisciplinary team (MDT) meets the individual needs of patients. Based on the concept of MDT, this study combined the theory and practice of flipped classroom teaching method to evaluate the teaching effect, so as to provide a basis and reference for the thinking transformation of medical students to clinicians. Methods The participants of the study were 760 clinical undergraduates in OGC training in Hainan Medical University from 2021 to 2023. A total of 760 students were divided into a control group and an observation group of 380 cases, each using the random number table method. The control group used traditional teaching methods, the observation group adopted the MDT combined with flipped classroom teaching model and organized dental postgraduates team to participate in the teaching task. A unified assessment of the teaching outcomes was conducted after 1 semester study duration. Results The basic theory, independent learning ability and case analysis scores of the observation group were higher than those in the control group, and the differences were statistically significant (P < 0.05). Except there was no statistically significant difference in literature searching ability between the two groups (P > 0.05), the other indicators of teaching satisfaction in the observation group were higher than those in the control group, and the difference was statistically significant (P < 0.05). The postgraduates team gave relatively good feedback to the MDT combined flipped classroom teaching model. Conclusion MDT combined flipped classroom teaching model had outstanding effect in OGC, this student-centered teaching method was a beneficial supplement to their clinical thinking and practical ability, and worth further promotion. Trial registration Not applicable.